Iron deficiency anaemia in patients with inflammatory bowel disease: National Consultant for Gastroenterology Working Group Recommendations - Kaniewska, Magdalena; Bartnik, Witold; Gonciarz, Maciej; Kłopocka, Maria; Linke, Krzysztof; Małecka-Panas, Ewa; Radwan, Piotr; Reguła, Jarosław; Rydzewska, Grażyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Anaemia is a common complication associated with inflammatory bowel diseases (Crohn’s disease and ulcerative colitis). It substantially impairs quality of life, makes therapy more complicated, and increases costs of treatment. It seems that anaemia therapy is suboptimal in this group of patients in the Polish population. The recommendations presented below provide iron deficiency anaemia management clues in patients with inflammatory bowel disease.